Eksperimen Pembelajaran Matematika dengan Bahan Ajar Interaktif Berbasis ICT Terhadap Hasil Belajar Ditinjau dari Keaktifan Siswa Pada Siswa Kelas VIII Semester Genap di SMP Muhammadiyah 7 Surakarta Tahun 2015/2016 - Wijaya, Resiana; , Prof. Dr. Budi Murtiyasa, M.Kom (2016)
This research aims to understand : (1) the learning influence with an interactive teaching materials based ICT of the mathematics learn resulth ,(2) the influence learn liveliness students level of the mathematics learn results , (3) the effect interaction between the learning method with interactive teaching materials based ICT and learn liveliness of the mathematics learn results. This research type is experiment research . The population of this research namely grade VIII students of SMP Muhammadiyah 7 Surakarta for the year 2015/2016 .The samples of this research are two classes which totaled 59 students.VIII C class as an experiment class using interactive teaching materials based ICT , while VIII D class as a cotrol class using expository method .The sample collection technique is by Cluster Random Sampling . The data collection technique is done with the test , poll and documentation. The data analysis technique using two roads variance analysis with not same cells. The results of reseach on α = 0.05 concluded that : (1) the are influence of learning with interactive teaching materials based ICT of the mathematics learn result with Fobs = 8.800792286 > Fa = 4.0 ; (2) there are influence of the learn liveliness level of the mathematics learn result with Fobs = 0.468450477 < Fa = 3.16 ; (3) there is no effect interaction among the learning method with teaching materials based ICT and learn liveliness of the mathematics learn results with Fobs = 0. 323000154 < Fa = 3.16 . It means the difference effect of the use of the learning method of the mathematics learn result not always depend on the learn liveliness level students , so does learn liveliness level students of the mathematics learn result does not depend on the methodology that was used. Keywords: active learning, Teaching materials, learning result.